Allevamento e produzione lattiero-casearia nella Lombardia dell’età moderna - Mocarelli, Luca (OS. Opificio della Storia, 2022)
The contribution deals with, in a necessarily synthetic way, the theme of breeding and dairy production in pre-industrial Lombardy, a crucial period for understanding the subsequent evolution as well. The discussion takes into account both the lower plain, examined through its relationships with the mountain range that call into question the fundamental role played by the “bergamini”, and the production of mountain cheeses, with particular reference to the Bresciano province.